1955
DOI: 10.1098/rspb.1955.0032
|View full text |Cite
|
Sign up to set email alerts
|

The determination of the individual equilibrium constants of the four intermediate reactions between oxygen and sheep haemoglobin

Abstract: It is now generally accepted that the equilibrium between oxygen (or carbon monoxide) and mammalian haemoglobin is expressible in terms of four intermediate reactions Hb 4 + O 2 ⇌ Hb 4 O 2 (equilibrium constant K 1 ), Hb 4 O 2 + O 2 ⇌ Hb 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1961
1961
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…This proposed mechanism of salt-bridge breaking became the basis for explaining the nature of the interaction energy of cooperativity that earlier had been identi ed as the difference in binding energy of the rst and fourth oxygen molecules (11,12), and was »3 kcal/iron. Perutz than continued by stating about the interaction energy (7 ): "Where in this large molecule should one look for that energy?…”
Section: The Perutz Mwc Modelmentioning
confidence: 99%
“…This proposed mechanism of salt-bridge breaking became the basis for explaining the nature of the interaction energy of cooperativity that earlier had been identi ed as the difference in binding energy of the rst and fourth oxygen molecules (11,12), and was »3 kcal/iron. Perutz than continued by stating about the interaction energy (7 ): "Where in this large molecule should one look for that energy?…”
Section: The Perutz Mwc Modelmentioning
confidence: 99%
“…9.4 to 12.4 torr when the protein concentration is raised from 0.5 to 62.5 gm/liter. For sheep hemoglobin in 0.2 M borate buffer, pH 9.1, 19°C, Roughton et al (13) found a concentration effect between 4 and 30 gm/liter, P0.5 at the latter being ca. 1.3 times greater than at the former concentration.…”
Section: The Protein Concentration-dependence Of the Oxygen-hemoglobimentioning
confidence: 99%
“…the special methods used by Roughton and his colleagues (6,13,22) for obtaining especially precise points at the bottom and top of the equilibrium curve. Fig.…”
Section: Po2(tor~)mentioning
confidence: 99%
“…The conclusions reached by Roughton, Otis & Lyster (1955) and by Gibson & Roughton (1957a) are considered in the light of the results.…”
mentioning
confidence: 99%
“…These observations must not only cover the range of saturation usually studied (5-95 % saturation) but must also include specially accurate observations between 0 and 1 % saturation and between 99 and 100 % saturation. Roughton, Otis & Lyster (1955) describe how the necessary observations may be made and how the values of K1, K2, K3, and K4 may be derived therefrom, together with their standard errors. They give actual sets of the constants for several samples of sheep haemoglobin, under the standard conditions of 190 C and pH 9*1.…”
mentioning
confidence: 99%